Configurable 2D nano-flows in mesoporous films using paper patches - Mercuri, Magalí (2018)
Designing and controlling spontaneous imbibition is becoming a key requirement for advanced devices, presenting a substantial scientific and engineering challenge. Here we describe an approach that allows directional imbibition into designed geometries. A set of custom domains based on paper microfluidics mold nano-imbibition in user-Defined shapes such as curvatures, corners, and vertices into mesoporous thin films; enabling localized chemical reactions with programmable designs. The method also achieves nano-size filtration, allows the generation and delivery of reagent gradients in a nanofluidic fashion, and it can be used as a reactor for the synthesis of patterned metallic nanoparticle arrays. By using this easyto-build hybrid platform, users can create functional nanofluidic domains in custom geometries and perform spatially shaped chemistry. The ability to integrate mesoporous nanofluidic generation and paper-based microfluidics has made the hybrid system an exciting candidate for versatile nanoflow applications.